Estimation of German KIR Allele Group Haplotype Frequencies - Solloch, Ute V.; Schefzyk, Daniel; Schäfer, Gesine; Massalski, Carolin; Kohler, Maja; Pruschke, Jens; Heidl, Annett; Schetelig, Johannes; Schmidt, Alexander H.; Lange, Vinzenz; Sauter, Jürgen (Frontiers in immunology, 2020)
The impact of the highly polymorphic Killer-cell immunoglobulin-like receptor ( ) gene cluster on the outcome of hematopoietic stem cell transplantation (HCST) is subject of current research. To further understand the involvement of this gene family into Natural Killer (NK) cell-mediated graft-versus-leukemia reactions, knowledge of haplotype structures, and allelic linkage is of importance. In this analysis, we estimate population-specific haplotype frequencies at allele group resolution in a cohort of = 458 German families. We addressed the polymorphism of the gene complex and phasing ambiguities by a combined approach. Haplotype inference within first-degree family relations allowed us to limit the number of possible diplotypes. Structural restriction to a pattern set of 92 previously described copy number haplotypes further reduced ambiguities. haplotype frequency estimation was finally accomplished by means of an expectation-maximization algorithm. Applying a resolution threshold of ½ , we were able to identify a set of 551 allele group haplotypes, representing 21 copy number haplotypes. The haplotype frequencies allow studying linkage disequilibrium in two-locus as well as in multi-locus analyses. Our study reveals associations between haplotype structures and allele group frequencies, thereby broadening our understanding of the gene complex.